Agile Treasury Operations During COVID-19 - World Bank (World Bank, Washington, DC, 2020)
Agile treasury operations are critical and essential to support responses to the spread and treatment of coronavirus disease 2019 (COVID-19). In many cases, this approach requires open and new ways of thinking ranging from making cash available to pay for public services, to processing and disbursing payments with minimum bureaucratic layers, to reporting in a timely and accurate manner to ensure transparency. Organized around three core areas of treasury operations, this note provides suggestions and guidance in three action areas: Ensure business continuity for treasury operations. Operationalize emergency arrangements. Manage the post-pandemic environment – recovery, reconstruction, and resilience.